Anti-displacement mobilities and re-emplacements: alternative climate mobilities in Funafala. Issue 14 (26th October 2022) - Farbotko, Carol
ABSTRACT: If there is a dominant global imaginary of climate change in low-lying islands, it is of displacement risk. This paper uses a mobilities perspective to consider anticipated displacement as a contested concept, reporting on emerging anti-displacement mobilities and re-emplacements in a rural, low-lying islet of Tuvalu named Funafala. Anti-displacement mobilities are defined as processes in which ideas, people and/or matter become mobile in order to counter anticipated displacement materially or symbolically, while re-emplacements are the new ideas, people and/or matter which together constitute the remaking of place through anti-displacement mobilities. These hitherto relatively unexplored mobilities and place-making practices are pragmatic and political acts that resist climate displacement, through reclaiming and redefining territory that has been categorised as highly exposed to climate change impacts and potentially unliveable. Grassroots anti-displacement and re-emplacement are interpreted in internal population mobility to Funafala, where Indigenous culture is being revitalised by re-emplacing homes and livelihoods in a remote, rural area. Mobilities are a way to repossess and revitalise place, and reclaim the meaning of habitability in the face of climate risk. These anti-displacement mobilities and re-emplacements reject dominant climate mobility regimes and reaffirm Indigenous rights and identities.